Examining risk and protective factors of problem gambling among college students in South Korea. (October 2019) - Jang, Soo Mi; Hong, Seunghye; Kim, Sophia Bohun; Sohn, Sunju
Abstract: Problem gambling has been recognized as an emerging problem among adolescents, however it is less understood among "emerging adults" (e.g., college students) despite the increased availability and accessibility of gambling venues to this age group. This study examines the effects of risk and protective factors on problem gambling among college students with the following two research questions: (1) what are the associations between risk factors (depressive symptoms, alcohol use, friends' attitude toward gambling) and problem gambling? and (2) what are the moderating roles of protective factors (ego-resiliency, perceived social support) on the associations between risk factors and problem gambling? Using hierarchical multiple regression analysis with data from three universities in South Korean ( n  = 512) and simple slope tests, this study found that all risk factors were significantly associated with problem gambling. Both protective factors showed moderating effects between depressive symptoms, alcohol use, and problem gambling. The findings suggest that improving ego-resiliency among college students and providing social support may prevent college students from developing gambling problems. Findings suggest the need to develop strength-based program, promote collaboration between campus and local agencies, and establish professional service agencies targeting problem gambling. Highlights: Despite increased accessibility of gambling among emerging adults, problem gambling is not understood. This study examines the effects of risk and protective factors on problem gambling among college students. Findings showed that depressive symptoms, alcohol use, and friends' attitude toward gambling affected problem gambling. Ego-resiliency and perceived social support moderated between depressive symptoms, alcohol use, and problem gambling. Improving ego-resiliency and providing social support may prevent college students from developing gambling problems.